2006
DOI: 10.1038/nm1386
|View full text |Cite
|
Sign up to set email alerts
|

Human sebaceous tumors harbor inactivating mutations in LEF1

Abstract: We found that one-third of human sebaceous tumors examined had double-nucleotide substitutions in the same LEF1 allele, irrespective of DNA mismatch repair status. The mutations impaired both LEF1 binding to beta-catenin and transcriptional activation, and are the first tumor-associated mutations that inactivate Wnt signaling. Mutant LEF1 not only inhibited expression of beta-catenin target genes but also stimulated expression of sebocyte markers, suggesting that it may determine the differentiated characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 15 publications
3
103
1
1
Order By: Relevance
“…Several observations show that Wnt signaling may promote the initiation of neoplastic process in many types of epithelial tumors via modulating the activity of stem cells. 34,35,37,45,47,50,51 It is also shown that BMP signaling inhibits proliferation of adult HF stem cells, while conditional ablation of the Bmpr1a gene triggers HF stem cells to proliferate leading to tumorigenesis. 43,46,52 However, it remains to be further clarified whether noggin-dependent modulation of BMP signaling directly affects Wif1 expression in the HF stem cells thus contributing to their reprogramming toward a neoplastic phenotype, or these changes occur at the level of transient amplifying cells during their differentiation pathway toward hair matrix keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several observations show that Wnt signaling may promote the initiation of neoplastic process in many types of epithelial tumors via modulating the activity of stem cells. 34,35,37,45,47,50,51 It is also shown that BMP signaling inhibits proliferation of adult HF stem cells, while conditional ablation of the Bmpr1a gene triggers HF stem cells to proliferate leading to tumorigenesis. 43,46,52 However, it remains to be further clarified whether noggin-dependent modulation of BMP signaling directly affects Wif1 expression in the HF stem cells thus contributing to their reprogramming toward a neoplastic phenotype, or these changes occur at the level of transient amplifying cells during their differentiation pathway toward hair matrix keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Both Wnt and Shh pathways are essential for HF development and cycling [for review, see 32 ], and, if abnormally activated, result in the development of a number of epithelial tumors. 26,[33][34][35][36][37][38] Interestingly, cells localized at the tumor placodes showed expression of the keratin 15 mRNA and Lhx2 protein, markers of the epithelial stem cells, 39,40 while their expression in fully developed tumors strongly decreased and was seen only in clusters of cells at the tumor periphery ( Figure 3, A and B). Keratinocytes of the tumor placodes also showed increased expression of the Wnt10b, Lef1, and nuclear ␤-catenin compared with the cells of fully developed tumors (Figure 3, A and B) and to the bulge cells of normal anagen HFs (data not shown).…”
Section: Tumors In K14-noggin Mice Show Stagedependent Differences Inmentioning
confidence: 99%
“…Perturbations in the levels of Axin, APC, β-catenin, LEF1 or TCF4, for example, contribute to the initiation and/or progression of several different types of cancer [7][8][9][10][11][12]. It is therefore not surprising that so much effort has gone into the development of new drugs based on our knowledge of Wnt signaling to treat disease.…”
Section: Canonical Wnt Signalingmentioning
confidence: 99%
“…It is not known how much full-length LEF-1 contributes to cancer progression, but the fact that its opposing dominant negative isoform is Diverse transcription regulation by LEF/TCFs L Arce et al actively suppressed is telling. A third example comes from the discovery of mono-allelic mutations in the LEF1 locus in human sebaceous tumors (Takeda et al, 2006). These mutations occur in the b-catenin-binding domain and essentially create a 'dnLEF-1' that can interfere with full-length LEF-1 produced from the wild-type allele as well as other co-expressed TCFs.…”
Section: Lef/tcf Antagonistsmentioning
confidence: 99%